2018
DOI: 10.3329/bjpt.v25i1.37186
|View full text |Cite
|
Sign up to set email alerts
|

<i>Colocasia hassanii</i> (Araceae), A new species of aroid from Bangladesh

Abstract: Colocasia hassanii, a new species of Araceae from Bangladesh, is described and illustrated. C. hassanii is closely related to C. esculenta (L.) Schott but differs from the later by the number of constriction (two) in spathe, presence of a sterile male zone in spadix, and bitter in taste. A morphological comparison between C. hassanii and C. esculenta is provided. IntroductionThe genus Colocasia Schott is represented by 13 species in the world (Yin, 2006) and eight species are found in Asia and Malay Archipelag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The flora of Bangladesh comprises a total of 3873 species of Angiosperms including 262 new records (Haque et al, 2012;Rahman et al, 2016;Rahman and Hassan, 2017;Islam and Rahman, 2017;Sourav et al, 2017;Ara, 2018;Ara and Hassan, 2018;Islam et al, 2018;Uddin et al, 2018;Uddin 2018;Alfasane et al, 2019Alfasane et al, , 2020Hossain et al, 2019;Huda et al, 2019) reported so far after the publication of Encyclopedia of Flora and Fauna of Bangladesh by Siddiqui et al (2007Siddiqui et al ( -2008 and Ahmed et al (2008Ahmed et al ( -2009.…”
Section: Introductionmentioning
confidence: 99%
“…The flora of Bangladesh comprises a total of 3873 species of Angiosperms including 262 new records (Haque et al, 2012;Rahman et al, 2016;Rahman and Hassan, 2017;Islam and Rahman, 2017;Sourav et al, 2017;Ara, 2018;Ara and Hassan, 2018;Islam et al, 2018;Uddin et al, 2018;Uddin 2018;Alfasane et al, 2019Alfasane et al, , 2020Hossain et al, 2019;Huda et al, 2019) reported so far after the publication of Encyclopedia of Flora and Fauna of Bangladesh by Siddiqui et al (2007Siddiqui et al ( -2008 and Ahmed et al (2008Ahmed et al ( -2009.…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh harbors a total of 3715 species of Angiosperms (Ahmed et al, 2008(Ahmed et al, -2009Rahman et al, 2016;Rahman and Hossain, 2017;Islam and Rahman, 2017;Sourav et al, 2017;Ara, 2018;Ara and Hassan, 2018;Uddin et al, 2018;Alfasane et al, 2019). During the botanical explorations in Sundarban Mangrove Forest of Bangladesh conducted in 2016-2018 by the authors, some specimens of Angiosperms were collected which did not match with any known plant species of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%